On effects that do occur versus effects that can be made to occur - Brauer, Markus; Kennedy, Kevin R. (Frontiers in Social Psychology, 2023)
Following Douglas Mook's lead we distinguish between research on “effects that can be made to occur” and research on “effects that do occur” and argue that both can contribute to the advancement of knowledge. We further suggest that current social psychological research focuses too much on the former type of effects. Given the discipline's emphasis on innovation, many published effects are shown to exist under very specific circumstances, i.e., when numerous moderator variables are set at a particular level. One often does not know, however, how frequently these circumstances exist for people in the real world. Studies on effects that can be made to occur are thus an incomplete test of most theories about human cognition and behavior. Using concrete examples, this article discusses the shortcomings of a field that limits itself to identifying effects that might—or might not—be relevant. We argue that it is just as much a scientific contribution to show that a given effect actually does occur as it is to provide initial evidence for a new effect that could turn out to be important. The article ends with a series of suggestions for researchers who want to increase the theoretical and practical relevance of their research.